2006
DOI: 10.1007/s11255-006-9004-x
|View full text |Cite
|
Sign up to set email alerts
|

Milk of Calcium Cyst Mimicking Renal Calculi: a Case Report

Abstract: A milk of calcium cyst mimicking renal stone in a 51-year-old man was presented to remind the possibility of milk of calcium when a well-defined round density was observed on the renal shadow of the plain abdomen film and the importance of graphics or CT scans taken in different positions to see the changes in the calcium gravidation to prevent unnecessary surgical interventions due to misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been reported that calcium may be present in the blood, bile duct, gastrointestinal duplication cysts, calyceal diverticula, pyelogenic cysts, obstructed pelvicalyceal systems, ureterocele, bronchogenic cysts, adrenal cysts, and breast cysts. [89] However, to best of our knowledge, there has been only one case report in literature of a case of tunica albuginea cyst presenting with calcium milk. [10]…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that calcium may be present in the blood, bile duct, gastrointestinal duplication cysts, calyceal diverticula, pyelogenic cysts, obstructed pelvicalyceal systems, ureterocele, bronchogenic cysts, adrenal cysts, and breast cysts. [89] However, to best of our knowledge, there has been only one case report in literature of a case of tunica albuginea cyst presenting with calcium milk. [10]…”
Section: Discussionmentioning
confidence: 99%